Rancang Bangun Sistem Rekomendasi Pariwisata Mobile dengan Menggunakan Metode Collaborative Filtering dan Location Based Filtering - Assaf Arief; Widyawan; Bimo Sunafri Hantono (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2012)
The innovations of electronic tourism (e-tourism) has gained attention in recent time, this result in the increased number of prototypes tourism applications web desktop based and mobile based. This research focuses on improving the quality of tourism service by building an automatic recommender system application that can run on mobile devices such as mobile phones, PDAs (Personal Digital Assistant), smartphone, iPad, etc. A tourism recommendation system is generally ask advice from officers with manually guide to help choose tourist spot will be visited, that were still deemed to be a subjective opinion. It becomes less precise in the use of informations, behavior, interests, tastes, and the rating to be conveyed to other tourists with similar preferences, which it’s the basis for providing content recommendations.This research objective are to build the mobile tourism recommendation system automation using the concept of personalization with collaborative filtering method and location based filtering for the alternate of manual systems (ask advice from officers of travel agency). The completion steps of this research are to make a mobile recommendation system with methods of collaborative filtering and location-based filtering, create a prototype mobile web-based applications, designing, manufacturing and the final process are improvement recommendations system.The results of this research is a mobile recommendation system application with platforms of JQuery Mobile, HTML 5, JavaScript, Ajax, PHP and MySQL. The test process are functionality testing, compatibility testing and system recommendations testing. It can be seen that the design of tourism recommendation system is able to provide tourist recommendation are suitable with the methods CF and LBF were applied.